Global neonatal nurses identify research priorities for improving neonatal outcome. Issue 2 (April 2021) - Broom, Margaret; Wainwright, Lynne; Spence, Kaye; Harris, Deborah L.; van den Hoogen, Agnes
Abstract: This study aimed to explore Neonatal nurses and midwives opinion regarding global research priorities. A prospective descriptive study was completed using survey methodology. Responses (n = 596) were received from 42 countries. Countries were divided into geographical areas: Africa 18 (3%), Asia 36 (6%), North America 156 (26%), South America 26 (4%), Europe 169 (28%) and Oceania 191 (32%). Sixteen research priorities were identified and categorised under two main themes with two key priorities being identified for each theme: 1) Improving clinical care of new-borns; key priorities are: Training and education needs of neonatal nurses, midwives and health workers; and Implementation of existing evidence into nursing practice: 2) The management and long-term outcomes of neonates; two key priorities are: Extreme prematurity: management and improving outcomes; and Pain: prevention management, and long-term outcomes of pain. Collaboration and research are needed to improve the dissemination of not only research evidence but practice methodologies that enable nurses to implement best practice.